Predictors of pulmonary exacerbations in patients with cystic fibrosis infected with multi-resistant bacteria. Issue 11 (14th July 2006) - Block, J K; Vandemheen, K L; Tullis, E; Fergusson, D; Doucette, S; Haase, D; Berthiaume, Y; Brown, N; Wilcox, P; Bye, P; Bell, S; Noseworthy, M; et al.
Abstract : Background: This study examined characteristics of adult and adolescent patients with cystic fibrosis (CF) to determine factors associated with an increased risk of pulmonary exacerbations. Methods: 249 patients with CF infected with multidrug resistant bacteria were recruited and prospectively followed for up to 4.5 years until they experienced a pulmonary exacerbation severe enough to require intravenous antibiotics. Multivariable regression analyses were used to compare the characteristics of patients who experienced an exacerbation with those who did not. Results: 124 of the 249 patients (50%) developed a pulmonary exacerbation during the first year and 154 (62%) experienced an exacerbation during the 4.5 year study period. Factors predictive of exacerbations in a multivariable survival model were younger age (OR 0.98, 95% CI 0.96 to 0.99), female sex (OR 1.45, 95% CI 1.07 to 1.95), lower forced expiratory volume in 1 second (FEV1 ) (OR 0.98, 95% CI 0.97 to 0.99), and a previous history of multiple pulmonary exacerbations (OR 3.16, 95% CI 1.93 to 5.17). Chronic use of inhaled corticosteroids was associated with an increased risk of exacerbation (OR 1.92, 95% CI 1.00 to 3.71) during the first study year. Conclusions: Patients who experience pulmonary exacerbations are more likely to be younger, female, using inhaled steroids, have a lower FEV1, and a history of multiple previous exacerbations. It is hoped that knowledge of these risk factors will allow better identification and closer monitoring of patients who are at high risk of exacerbations.